MONTESQUIEU A RZYMSKA DYSCYPLINA WOJSKOWA: POGLĄDY, INTERPRETACJE I ŹRÓDŁA POZNANIA - Faszcza, Michał Norbert (Zeszyty Prawnicze, 2016)
Montesquieu and Roman Military Discipline: Opinions, Interpretations, and Sources Summary Montesquieu’s influence on the development of modern public law is undisputed, but he also played a very important role in shaping the perception of the Roman art of war. Like Machiavelli, he devoted a considerable amount of attention to Roman disciplina militaris. His comments were quite general, but they exerted a substantial influence on the opinions of scholars of military discipline. Along with Lipsius and Machiavelli, he was one of the most cited authors, and his perception of military discipline was even reflected in some of the arrangements employed in the French army under the First Republic. Research on the reception of Roman ideas on the art of war usually stops at the Middle Ages, but Montesquieu’s work as a writer and his impact on later scholars are the best justification for studying his opinions on this issue.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />